Quality Risk Management in Pharmaceutical Industry-A Overview - Vartak, R.P.; Bhagure, G.R. (Asian Journal of Chemistry, 2012)
Risk is defined as combination of the probability of occurrence of harm and severity of that harm. Quality risk management is a systemic process for the assessment, control, communication and review of risk to the quality of the medicinal product. It can be applied both proactively and retrospectively. The quality risk management system should ensure that the evaluation of the risk to quality is based on scientific knowledge, experience with the process and ultimately links to the protection of the patient. The risk management is applied to different aspects of the pharmaceutical industry. These aspects includes development, manufacturing, distribution, inspection, preparation of the quality part of the marketing authorization dossiers and handling of suspected quality defects throughout the life-cycle of the drug substance, drug product, biological, biotechnological products, raw materials, solvents, excipients, packing and labeling materials. The risk to its quality is just one component of the overall risk. The quality of the product should be maintained throughout the life-cycle of the product.